Soil Organic Matter Mineralization as Driven by Nutrient Stoichiometry in Soils Under Differently Managed Forest Stands - Gan, Huei Ying; Schöning, Ingo; Schall, Peter; Ammer, Christian; Schrumpf, Marion (Frontiers in Forests and Global Change, 2020)
Nutrient contents of soil organic matter in forests vary with regional differences in soil types, and can be modified by forest management. Variation of organic carbon (OC)-to-nutrient ratios in soils supposedly alters microbial carbon and nutrient use efficiencies and the rates of OC-to-nutrient mineralization. Here, we studied mineralization rates of carbon (C), nitrogen (N), phosphorus (P) and sulfur (S) for topsoil samples from differently managed forest plots in Germany. Samples were incubated for two weeks in microlysimeters under controlled conditions. CO2 respiration, leachable dissolved organic carbon (DOC), nitrate (NO3-), ammonium (NH4+), sulphate (SO42-) and phosphate (PO43-) were determined as net organic C (OC) and nutrient mineralization rates. We hypothesized that in soils with high C-to-nutrient ratios, soil microbes may mobilize relatively more OC as CO2 or DOC than nutrients to meet their nutrient and that forest type influences the stoichiomertry of SOM mineralization by altering the ratios of C-to-nutrients in soils. Results showed that CO2-release rates were proportional to soil OC, but when normalized to microbial biomass C, they increased, similar to DOC leaching rates, with soil OC-to-N ratios. However, higher soil OC-to-nutrient ratios did not go along with reduced nutrient leaching. Instead, when normalized to soil OC, the largest amounts of N, P and S were leached in the most nutrient poor region, so that sites with highest soil OC-to-nutrient ratios had the smallest OC-to-nutrient mineralization ratio. Forest type affected soil stoichiometry only in the most nutrient poor region with smaller OC-to-nutrient ratios and OC-normalized DOC leaching rates under deciduous than coniferous forest sites. However, in the two other study regions tree species had a significant effect on N and S leaching rates and the ratio of OC-to-nutrient leaching despite similar stoichiometry. Overall, our study suggests that increasing nutrient scarcity enhances microbial based CO2 and DOC production, possibly because of increased energy demand for enzyme production to reach and mobilize nutrients, thereby allowing for high nutrient leaching rates despite small total stocks. Forest management affected OC-to-nutrient mineralization rates mostly via tree species selection, but differences were not caused by soil stoichiometry but rather other ecological differences between forest types.